Bedside intra-aortic balloon pump implant in cardiac intensive care unit. (2nd May 2022) - Baldetti, L; Boccellino, A; Barone, G; Gallone, G; Venuti, A; Gramegna, M; Calvo, F; Pazzanese, V; Sacchi, S; Cappelletti, AM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Intra-aortic balloon pumping (IABP) support has been progressively reappraised, especially for the acute decompensated heart failure (ADHF) cardiogenic shock (CS) scenario(1). IABP features an easy implantation technique and can rapidly be deployed bedside. This avoids the need of patient transfer to the catheterization laboratory (CathLab) and the inherent risk of destabilization and makes it an attractive approach in case of unstable hemodynamics. However, despite decades of IABP utilization, no data is available on the safety and feasibility of the IABP bedside implant. Aim: Aim of this study was to assess the safety and feasibility of bedside IABP implant and to characterize the phenotype of patients who receive this support. Methods: We retrospectively reviewed all consecutive patients who received bedside IABP in the last 12 months. For comparison purposes we also selected all consecutive patients who underwent IABP implant in the CathLab in the same timespan. Major vascular complication was defined as thoracic aortic dissection, access-related vascular injury leading to either death, unplanned percutaneous/surgical intervention, need for ≥4 blood unit transfusions, amputation for distal embolization, or irreversible end-organ damage. All analyses were performed with R. Results: A total of 77 patients were included: 22 (28.6%) received bedside, and 55 (71.4%) CathLab IABP implant. A total of 62 (81.6%) patients were male, age was 73 (64-79) years, and invasive mechanical ventilation was required in 54 (70.1%): no differences were observed between groups. Bedside IABP implant was guided by trans-esophageal echocardiography in 10 (45.5%) and trans-thoracic echocardiography in 12 (54.5%) patients. Patients in the bedside IABP cohort had more often pre-existing heart failure (HF, 72.7 vs 32.7%; p=0.001), presented with ADHF (45.5 vs 12.7%; p=0.002) and in overt CS (77.3 vs 34.5%; p<0.001). They also demonstrated lower systolic arterial pressure [90.0 (86.2-102.5) vs 123.0 (104.5-140.0) mmHg; p=0.007], lower left ventricular ejection fraction [LVEF, 20 (15-25) vs 25 (20-35)%; p<0.001] and higher serum lactate [5.4 (3.6-8.5) vs 2.0 (1.3-3.7) mmol/L; p=0.001]. Despite worse baseline conditions than the CathLab group, bedside IABP cohort experienced a similar in-hospital mortality (22.7 vs 18.2%; p=0.649), similar major bleeding events (27.3 vs 12.7%; p=0.124), and similar major vascular complications (4.5 vs 5.5%; p=0.871). No patient experienced cerebrovascular events. Conclusion: In this single-center experience, bedside IABP implant appeared safe and feasible. No difference was observed in terms of in-hospital mortality or major vascular complications between the bedside and CathLab groups, despite worse clinical conditions in the bedside IABP group. This strategy was often employed in critically-ill patients with ADHF with CS, were IABP use is increasing.